2009
DOI: 10.1371/journal.pone.0008503
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Proteasome Inhibitors Using a High-Content Cell-Based Screening System

Abstract: The regulated degradation of damaged or misfolded proteins, as well as down-regulation of key signaling proteins, within eukaryotic and bacterial cells is catalyzed primarily by large, ATP-dependent multimeric proteolytic complexes, termed proteasomes. Inhibition of proteasomal activity affects a wide variety of physiological and pathological processes, and was found to be particularly effective for cancer therapy. We report here on the development of a novel high throughput assay for proteasome inhibition usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 42 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…A recent study [34] has suggested that the sensitivity to proteasome inhibition is associated with the status of p53. However, apoptosis triggered by proteasome inhibition appears to be independent of p53 in prostate cancer [35], multiple myeloma [30], and colon cancer cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study [34] has suggested that the sensitivity to proteasome inhibition is associated with the status of p53. However, apoptosis triggered by proteasome inhibition appears to be independent of p53 in prostate cancer [35], multiple myeloma [30], and colon cancer cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, TMPRSS4 activates cell-mediated fusion of MERS-CoV and SARS-CoV, but it does not activate infection. Other TTSPs, TMPRSS11a, and TMPRSS11e, activate S-protein fusion of MERS-CoV, while TMPRSS11a activates SARS-CoV fusion S-protein, which causes infection (Tang et al 2020 ; Kam et al 2009 ). Human airway trypsin-like protease (HAT) known as TMPRSS11d, can activate MERS-CoV (Tang et al 2020 ; Kam et al 2009 ; Bertram et al 2011 ).…”
Section: Human Cellular Receptors As Targets Of Coronavirusesmentioning
confidence: 99%
“…Other TTSPs, TMPRSS11a, and TMPRSS11e, activate S-protein fusion of MERS-CoV, while TMPRSS11a activates SARS-CoV fusion S-protein, which causes infection (Tang et al 2020 ; Kam et al 2009 ). Human airway trypsin-like protease (HAT) known as TMPRSS11d, can activate MERS-CoV (Tang et al 2020 ; Kam et al 2009 ; Bertram et al 2011 ). Although, transient expression of TMPRSS2, TMPRSS4, TMPRSS11a, TMPRSS11d, and TMPRSS11e enhances SARS-CoV-2 S-protein-mediated cell–cell fusion, these proteases activating the S-protein for infection are yet to be investigated (Ou et al 2020 ; Tang et al 2020 ).…”
Section: Human Cellular Receptors As Targets Of Coronavirusesmentioning
confidence: 99%
“…For control group, Ad-Red was substituted for TE6 or TE7 adenovirus in the p53 control and Rb control, respectively. 12-24h later, 10 μl cells were collected and plated in 384 well plates containing 10 μl DMEM with 20 μM compounds, making the final screening compound concentration of 10 μM, which is a concentration commonly used in cell-based high-throughput screens [ 13 , 14 ]. Experimental wells were plated with 2000 p53-TE6 cells and 2000 Rb-TE7 cells per well.…”
Section: Methodsmentioning
confidence: 99%